Women’s preferences concerning digital games: identification of relevant characteristics through descriptive and formal concept analysis - Ferreira, Ronan L. R.; Machado, Mônica da Consolação; Song, Mark Junho; Ishitani, Lucila (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2025.9844, 2025)
Introduction: While girls love to play games, many games still fail to engage them properly. Game development is still dominated by a male perspective, perpetuating stereotypes and making it difficult for women to enter the industry. Objective: Therefore, this study explores the characteristics of digital games considered relevant for women, aiming to encourage their engagement with these games. Methodology or Steps: Female participants completed an online questionnaire to provide data on their perceptions about game characteristics to achieve this objective. The collected data were analyzed using Descriptive Analysis and Formal Concept Analysis (FCA). Results: Based on the results from FCA, we identified and discussed significant relationships among the characteristics considered relevant in games for women.